2006
DOI: 10.1167/iovs.06-0214
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Genome-Wide Linkage Scan in Keratoconus Sib Pair Families

Abstract: These results indicate that one or more loci may contribute to keratoconus susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 23 publications
5
77
1
5
Order By: Relevance
“…16 Interestingly, other suggestive loci on 5q have been identified also for KTCN. 13,[25][26][27] Our 5q31.1-q35.3 linkage region overlapped two of them, 5q31 and 5q32-q33 in the Caucasian/Hispanic and the Southern Italian populations, respectively 13,26 (Figure 1c). These findings further indicate that the 5q31.1-q35.3 locus might be truly linked with KTCN.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…16 Interestingly, other suggestive loci on 5q have been identified also for KTCN. 13,[25][26][27] Our 5q31.1-q35.3 linkage region overlapped two of them, 5q31 and 5q32-q33 in the Caucasian/Hispanic and the Southern Italian populations, respectively 13,26 (Figure 1c). These findings further indicate that the 5q31.1-q35.3 locus might be truly linked with KTCN.…”
Section: Discussionmentioning
confidence: 91%
“…[12][13][14][15] Whole-exome sequencing (WES), which allows determination of the rare and unique coding sequence variants in an individual personal genome, can be also utilized in familial studies. However, due to a number of candidate genes generated by linkage analysis or WES, the evaluation of each individual variant is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 LOX (locus 5q23.2), the gene encoding lysyl oxidase (LOX) enzyme, which is involved in collagen and elastin cross-linking, have also been related to keratoconus. 57 Association between single-nucleotide polymorphisms in the hepatocyte growth factor (HGF) gene and keratoconus has been found. 58,59 Multiple studies have reported a statistically significant risk of developing keratoconus in patients with polymorphism of the gene in charge of the IL-1β coding (IL-1B-31 T4C and IL-1B-511 C4T); 60,61 nevertheless, a recent study in a different population found no clear relation between the IL-1B gene polymorphism and the receptor antagonist IL-1 (ILRN VNTR) with the possibility of keratoconus development.…”
Section: Geneticsmentioning
confidence: 99%
“…Genetic studies have led to the identification of several loci on many chromosomes, linked to KTCN, including 1p36.23-36.21, 2p24, 2q13, 3p14-q13, 5q14.3-q21.1, 5q21.2, 5q32-q33, 9q34, 13q32, 14q11.2, 14q24.3, 15q15.1, 15q22. 33-24.2, 16q22.3-q23.1, 17p13, 20q12 [13][14][15][16][17][18][19][20][21][22][23][24][25]. To date, most of the identified loci have not been replicated in other populations.…”
Section: Keratoconusmentioning
confidence: 99%